Ineffective Ventilation in A Neonate with A Large Pre-Carinal Tracheoesophageal Fistula and Bilateral Pneumonitis-Microcuff Endotracheal Tube to Our Rescue! - Gupta, Anju; Gupta, Nishkarsh (Journal of Neonatal Surgery, 2016)
Tracheoesophageal fistula (TEF) is one of the most common congenital anomaly requiring surgical correction in neonatal period. The important goal of airway management is to avoid excessive gastric distension and ensure adequate ventilation prior to surgical ligation of the fistula. If a large fistula is present close to carina, excessive loss of delivered tidal volume may lead to ineffective ventilation. In addition, gastric distension elevates diaphragm and diminishes the lung compliance. If lung compliance is already impaired due to pre-existing lung pathology, situation becomes much more demanding. We report the successful airway management of a patient with large precarinal fistula and bilateral pneumonitis using the novel Microcuff tube. The unique design of microcuff makes it suitable to be used for this purpose. To the best of our knowledge, the use of microcuff ETT for perioperative airway management in case of a large precarinal fistula in a neonate with respiratory pathology has not been reported in the past.